Rules and Reasoning 7th International Joint Conference, RuleML+RR 2023, Oslo, Norway, September 18-20, 2023, Proceedings - Fensel, Anna.; Ozaki, Ana.; Roman, Dumitru; Soylu, Ahmet (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book constitutes the refereed proceedings of the 7th International Joint Conference on Rules and Reasoning, RuleML+RR 2023, held in Oslo, Norway, during September 18-20, 2023. The 13 full papers and 3 short papers included in these proceedings were carefully reviewed and selected from 46 submissions. They focus on all aspects of theoretical advances; novel technologies; innovative applications; knowledge representation; reasoning with rules; and research, development, applications of rule-based systems. .
Papers -- Extension of Regression Tsetlin Machine for Interpretable Uncertainty Assessment -- GUCON: A Generic Graph Pattern based Policy Framework for Usage Control Enforcement -- Combining Proofs for Description Logic and Concrete Domain Reasoning -- Notation3 as an Existential Rule Language -- Fine-tuning Large Enterprise Language Models via Ontological Reasoning -- Layerwise Learning of Mixed Conjunctive and Disjunctive Rule Sets -- Analyzing Termination for Prev-Aware Fragments of Communicating Datalog Programs -- Marrying Query Rewriting and Knowledge Graph Embeddings -- Lore: Educational Deductive Database System -- Comparing State of the Art Rule-Based Tools for Information Extraction -- A Case Study for Declarative Pattern Mining in Digital Forensics -- Semantic Role Assisted Natural Language Rule Formalization for Intelligent Vehicle -- FreeCHR: An Algebraic Framework for CHR-Embeddings -- Explaining the optimal trajectories -- Abstract Domains for Database Manipulating Processes -- Extracting Interpretable Hierarchical Rules from Deep Neural Networks' Latent Space.
Keywords: Computer science; Information technology -- Management; Database management; Logic programming; Natural language processing (Computer science).; Expert systems (Computer science).; Theory of Computation; Computer Application in Administrative Data Processing; Database Management; Logic in AI; Natural Language Processing (NLP).; Knowledge Based Systems